Association Between Carbamazepine Toxicity, Liver Bile Duct Injury, Granuloma and Inflammatory Cells Infiltration in Female Mice - A.T. Nawar R. Jaber1 , Nahla A. Al-Bakri2 , A.T. Ola Al-Bhadly3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The liver is an important organ in the body that can be affected by many drugs and toxins. The hepatotoxinscan cause oxidant stress that lead to activation of inflammatory cells and cause liver damage. Drug inducedbile duct injuries are related to drug toxicity, multiple drugs have been known to cause the development ofliver granulomas. Carbamazepine (CBZ) among other antiepileptic drugs is believed to cause hepatic injury.In this study we investigated the effect of (CBZ) 20mg/kg/day on female mice liver after 14 and 30 daysof treatment. The histological findings showed that (CBZ) can cause histological alterations in the livercomponents such as bile duct proliferation, biliary hypertrophy, ductopenia, inflammatory cells infiltrationand granulomas.